Oral sulforaphane increases Phase II antioxidant enzymes in the human upper airway - Riedl, Marc A (Clinical immunology (Orlando, Fla.), 2009)
BACKGROUND: Cellular oxidative stress is an important factor in asthma and is thought to be the principle mechanism by which oxidant pollutants such as ozone and particulates mediate their pro-inflammatory effects. Endogenous Phase II enzymes abrogate oxidative stress through the scavenging of reactive oxygen species and metabolism of reactive chemicals